Using game engines and graphic technologies for ray-tracing in future wireless (2014)
We present here a discussion about the use of 3D ray-tracing (RT) techniques based on game engines and graphic technologies to derive the multipath channel. Our approach harnesses the power of video game development engines to provide the urban 3D model and 3D RT for exploration and analysis of multipath channel for a wide frequency range in different complex outdoor scenarios. The advantage of this approach is that it efficiently utilizes the potential and capabilities in the graphical processing units (GPUs) and provide high performance in computing time with accurate results. We demonstrate the usefulness of this approach using our 3D RT in different applications. We show simulation results and compare them with measurements, obtaining a good fit. © 2014 European Association on Antennas and Propagation.